2021
DOI: 10.3390/ijerph18094945
|View full text |Cite
|
Sign up to set email alerts
|

Exposures in the Indoor Environment and Prevalence of Allergic Conditions in the United States of America

Abstract: Our study examines the association of the presence of mildew, cockroaches, and pets in homes as well as household dust allergens with the prevalence and/or severity of allergic diseases. No study has concurrently assessed home environment exposures in relation to allergic conditions in the general US population. Data from 5409 participants from the 2005–2006 National Health and Nutrition Examination Survey (NHANES) living in their current homes for ≥one year were analyzed. Multivariate logistic regression anal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Evidence suggests that apart from the common allergens such as pollens, house dust, or animal dander, exposure to tobacco smoke, 7 antibiotics, 8,9 and chemicals 10 during pregnancy are also associated with the risk of AR to offspring. In developing countries, particularly in South‐East Asia, the prevalence of AR is also high, for example, the prevalence of AR is between 11 and 18% in China and between 6% and 22% in India where environmental factors such as outdoor and indoor air pollution are the predominant risk factors 11–17 . However, the exact prevalence of AR often varies significantly among studies, even in studies performed in the same geographical locations.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence suggests that apart from the common allergens such as pollens, house dust, or animal dander, exposure to tobacco smoke, 7 antibiotics, 8,9 and chemicals 10 during pregnancy are also associated with the risk of AR to offspring. In developing countries, particularly in South‐East Asia, the prevalence of AR is also high, for example, the prevalence of AR is between 11 and 18% in China and between 6% and 22% in India where environmental factors such as outdoor and indoor air pollution are the predominant risk factors 11–17 . However, the exact prevalence of AR often varies significantly among studies, even in studies performed in the same geographical locations.…”
Section: Introductionmentioning
confidence: 99%
“…House dust mites (HDMs) are a primary allergen worldwide, and preceding studies conducted to explore this have proven that more than 90% of allergic rhinitis (AR) patients in central China have been triggered with the aid of HDMs (Wang et al, 2017). A multivariate logistic regression analysis conducted by Gasana et al (Gasana et al 2021) for the prevalence and severity of allergic diseases arising from indoor exposure to dust mites in American households demonstrated that the presence of dust Der f 1 was responsible for asthma and/or severe wheezing. Therefore, understanding the indoor transmission mode and concentration distribution of dust mite allergens is essential to investigation of the pathogenesis of allergic diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Asthma is the most common chronic disease of childhood in the United States (US) and a common cause of hospitalization in children and adolescents. 1 It can cause lifelong disability and has both genetic and environmental risk factors. 2 Additionally, environmental triggers present in places where people with asthma spend most of their time can trigger exacerbations limiting meaningful activities and impairing quality of life (QOL).…”
Section: Introductionmentioning
confidence: 99%